Ag-Incentives Consortium: Improved data and practices in agricultural policy measurement - CGIAR Research Program on Policies, Institutions, and Markets (2017)
The creation of an international consortium among several international organizations in the field of agricultural policy monitoring and measurement is the result of a multi-year trust building exercise, leading to actual changes in partner practices to guarantee the highest quality of data. There is a growing end user base who use Ag-Incentives as their source of information on farm policies. Indeed, governments, NGOs and others are using the website as their information source for policy dialogue.